The Crescent on the Temple : the Dome of the Rock as Image of the Ancient Jewish Sanctuary. - Berger, Pamela, 1940-2024 (Studies in religion and the arts., 2012)
"The Crescent on the Temple" elucidates how the Dome of the Rock came to stand for the Temple of Solomon in Christian, Muslim, and Jewish art. That "Temple," represented as the Muslim shrine, is often surmounted by a crescent.